Current Issues and Challenges of Fingerprint Recognition - Mohamad Jamil, Amirah Hanani Binti (Prosiding International conference on Information Technology and Business (ICITB), 2017)
As we familiar with, fingerprint recognition technique is the dominant technology in the biometric market. A number of recognition techniques have been used to perform fingerprint matching. Straight forward matching between the fingerprint pattern to be identified and most of us already knew patterns would not serve well due to its high sensitivity to errors (such as various noises, damaged fingerprint areas, or the finger being placed in different areas of fingerprint scanner window and with different orientation angles, etc.). Keywords: fingerprint matching; pattern-based method; minutiae-based method; current issues;